Signifikansi Konseling Pastoral Dan Komunikasi Interpersonal: Atasi Trauma Pekerja Migran Indonesia - Sandra Latief; Edi Soerjantoro; Mario Alberto Manodohon; Yehuda Indra Gunawan (Vox Dei: Jurnal Teologi dan Pastoral, 2023)
This research examines the problem of trauma experienced by Indonesian Migrant Workers who have returned to Indonesia in the Special Capital Region of Jakarta. The research focused on the factors that influence the trauma of Indonesian Migrant Workers, namely pastoral counseling and interpersonal communication so that the purpose of this research can be realized, namely, to find out the significance of these factors to the existing trauma problem. The main problem expressed in this study is the support of empirical facts in the structure of the relationship between variables that directly or indirectly influence the trauma of Indonesian Migrant Workers. This research uses quantitative methods. The data collection technique used a questionnaire with a Likert scale model and the number of respondents was 93 Indonesian Migrant Workers. Data processing techniques through a path analysis model using the Smart Partial Least Squares (Smart PLS) program. The results of the research based on hypothesis testing show that: Pastoral counseling has a significant effect on trauma; Interpersonal communication has a significant effect on trauma; Pastoral counseling and interpersonal communication simultaneously have a strong and significant effect on trauma.